Enhancing problem-solving and collaboration skills through role-playing in problem-based learning - Fatma Aisyah Ayu; Yayuk Mulyati; Sri Wulan Romdaniyah; Indra Fardhani; Rini Anggi Arista; Mochammad Hannats Hanafi Ichsan (Universitas Muhammadiyah Malang, 2026)
: Background-Low levels of problem-solving and collaboration skills among junior high school students remain a significant challenge in science learning, particularly due to limited interactive and contextual learning approaches. Objective-This study aims to analyze the potential of integrating role playing into problem-based learning (PBL-RP) to improve junior high school students' problem-solving skills (PSS) and collaboration skills (CS). Method-The research method used was a quasi-experimental design with a non-equivalent control group, involving two classes: an experimental class using the PBL-RP model and a control class using the PBL model. Results-The results showed that the application of PBL-RP was effective in improving students' PSS with a moderate N-gain score, while the PBL class only achieved a low score. The highest indicator of improvement was in the aspect of understanding problems. In addition, student CS in the experimental class increased significantly based on the results of teacher observations, but the increase was not seen in peer assessments due to differences in perception and depth of observation. Conclusion-Overall, the results of the study confirm that PBL-RP has the potential to simultaneously strengthen students' higher-order thinking and collaborative skills and is relevant to 21st-century learning to foster contextual, reflective, and student-centered learning processes.